Genetic Polymorphism of NRAMP-1 and iNOS genes in Giriraja and Indigenous Chicken - Singh, Sanabam Robin; Naveen, Kumar S; Inamdar, Basavraj; Bhajantri, Shankarappa; Patil, Vivek M; Malathi, V (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was conducted to identify and compare the genetic polymorphisms of Natural Resistance Associated Macrophage Proteins-1(NRAMP-1) and Inducible Nitric Oxide Synthase (iNOS) genes among Giriraja and Indigenous chicken. Blood samples were collected from 100 each of Giriraja and Indigenous chicken and the DNA was isolated by Phenol: Chloroform: Iso-amyl alcohol (25:24:1) method. Published primers were employed to amplify NRAMP-1 (exon 11) and iNOS (intron 24) genes. RFLP analyses of NRAMP-1 and iNOS genes were conducted utilizing SacI and AluI restriction enzymes, respectively. For NRAMP-1, the frequencies of TT, TC and CC genotypes were 0.16, 0.47 and 0.37, respectively in Giriraja and 0.10, 0.57 and 0.33, respectively in Indigenous chicken. The frequencies of T and C alleles were 0.395 and 0.605, respectively in Giriraja chicken and 0.385 and 0.615, respectively in Indigenous chicken. For iNOS, the frequencies of TT, TC and CC genotypes were 0.26, 0.36 and 0.38, respectively in Giriraja and 0.20, 0.53 and 0.27, respectively in Indigenous chicken. The frequencies of T and C alleles were 0.440 and 0.560, respectively in Giriraja and 0.465 and 0.535, respectively in Indigenous chicken. The present study detected 5 SNPs (T>C transition at 128 bp; T>G transversions at 140 bp and 141 bp; T>C transition at 189 bp; A>G transition at 393 bp) in C allele of NRAMP-1 gene of Giriraja compared to Indigenous chicken and 2 SNPs (G>A transition at 107 bp and T>C transition at 130 bp) in C allele compared to T allele of iNOS gene in both Giriraja and Indigenous chicken.